Gerakan Julid Fisabilillah - Santi, Selvia (Jurnal ICMES, 2024)
Israel's military aggression against the Gaza Strip, which began on October 7, 2023, has become one of the most important issues in the world thanks to the role of social media, which massively disseminates events on the ground and counters the mainstream media narrative, which tends to be pro-Israel. Social media has been actively used by internet citizens around the world to defend Palestine. In Indonesia, a movement emerged on social media called "Julid Fisabilillah" which opposed pro-Israel internet citizens. This article will analyze this movement using the New Social Movement theory. The findings in this article are that the “Julid Fisabilillah” movement is a mass movement that is coordinated to raise global social issues based on human and religious values to fight against Israel's oppression of the Palestinian people.